Year-round growth potential and moisture stress tolerance of buckwheat (Fagopyrum esculentum L.) under fragile hill ecosystems of the Eastern Himalayas (India) - Rangappa, Krishnappa; Rajkhowa, Dipjyoti; Layek, Jayanta; Das, Anup; Saikia, Uday Sankar; Mahanta, Kaberi; Sarma, Anjan Kumar; Moirangthem, Prabha; Mishra, Vinay Kumar; Deshmukh, Nishant Anandrao; Rajbonshi, Namrata; Kandpal, Basant K. (Frontiers in Sustainable Food Systems, 2023)
Under changing climate, the fragile ecosystems of Eastern Himalaya (EH) are persistently challenged by prolonged dry spells and erratic rainfall. Identification of suitable high yielding crop having higher moisture stress tolerance and adaptability is paramount for the region.Although the region received good amount of rainfall in the rainy season, the winter months viz., November to March rarely received any rain. Even within the rainy season, there are several intermittent drought spell which hinders the crop productivity. Present study with field and microcosm experiments assessed the year-round cultivation potentiality and extent of moisture stress tolerance in lesser-known buckwheat crop of the region. Sowing of buckwheat between mid-September to mid-December produced better grain yield, highest being with sowing in October (9.83 q ha -1 ) and the crop found suitable to grow all through the year for higher green biomass (12.6-38.4 q ha -1 ). Moisture stress tolerance of buckwheat was significantly enhanced by increased total root length and root surface area to the tune of 12.4% and 34.7% respectively.Increased photo-protective carotenoids, chlorophyll b and favourable stomatal attributes with substantial epicuticular wax were significantly imparted the moisture stress tolerance in buckwheat. Leaf proline was 25.4% higher and total soluble protein, reducing sugar and cell membrane stability was reduced to 29.2%, 38.1 and 36.5% over control respectively.Significantly lower rate of water loss (25.6%) noted under moisture stress over control with its stomatal and non-stomatal adaptations and with versatile pollen structural traits under moisture stress make buckwheat potential stress tolerant and economical crop for EH of India.